Characterization of materials and conservation of Viceroy Antonio Manso de Velasco de Superunda - Petrick Casagrande, Susana Margarita (2018)
In this work we present the first results obtained from the caractherization of materials, diagnosis and intervention of the portrait of Don Antonio Manso de Velasco, Count of Superunda, viceroy of Peru in the second half of the 18th century, a work executed by Cristobal Lozano, renowned colonial painter. The characterization techniques used were optical microscopy, drop chemical analysis, scanning electron microscopy and EDX analysis.